2014
DOI: 10.1093/aob/mcu042
|View full text |Cite
|
Sign up to set email alerts
|

New views of tapetum ultrastructure and pollen exine development in Arabidopsis thaliana

Abstract: This high-quality structural information, interpreted in the context of recent functional studies, provides the groundwork for future mutant studies where tapetum and microspore ultrastructure is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
129
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 51 publications
5
129
2
Order By: Relevance
“…Sporopollenin is synthesized in tapetal cells, secreted to locules, and transferred to the microspore surface (Owen and Makaroff 1995;Quilichini et al, 2014). Besides the failure of exine formation in kns4, we revealed that the sporopollenin is abnormally deposited on the surface of tapetal cell walls, which is in contact with the developing exine of microspores (Figs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sporopollenin is synthesized in tapetal cells, secreted to locules, and transferred to the microspore surface (Owen and Makaroff 1995;Quilichini et al, 2014). Besides the failure of exine formation in kns4, we revealed that the sporopollenin is abnormally deposited on the surface of tapetal cell walls, which is in contact with the developing exine of microspores (Figs.…”
Section: Discussionmentioning
confidence: 88%
“…2, B and H, respectively). Moreover, the protoplast of the wild-type PMCs was often detached from the primary cell wall, although this is likely to be a sample preparation artifact frequently observed during this developmental stage in wild type (Quilichini et al, 2014). Interestingly, this was never observed in mutant PMCs, perhaps indicating some structural differences in connectivity between the plasma membrane-cell wall interface between wild type and mutants.…”
Section: Kns4 Is Required For Separation Of Pmcs and Microspores In Amentioning
confidence: 99%
“…Tapetum-specific organelles, including the tapetosomes and elaioplasts, showed no difference in the wild type and mon1, excluding the possible involvement of MON1 in their biogenesis (Supplemental Fig. S5, B and C; Quilichini et al, 2014). These results suggest that MON1 is crucial for the proper timing of tapetal PCD.…”
Section: The Mon1 Mutation Causes Delayed Pcd In Tapetal Cellsmentioning
confidence: 83%
“…Sporopollenin precursors are synthesized in the tapetum, a metabolically active anther secretory tissue that surrounds the anther locule where microspores and pollen grains develop (Ariizumi and Toriyama, 2011;Quilichini et al, 2014aQuilichini et al, , 2015a. The morphological and cellular events involved in pollen and pollen wall development have been most thoroughly studied in Arabidopsis and rice (Oryza sativa; Sanders et al, 1999;Scott et al, 2004;Ariizumi and Toriyama, 2011;Shi et al, 2015).…”
mentioning
confidence: 99%
“…The morphological and cellular events involved in pollen and pollen wall development have been most thoroughly studied in Arabidopsis and rice (Oryza sativa; Sanders et al, 1999;Scott et al, 2004;Ariizumi and Toriyama, 2011;Shi et al, 2015). A recent detailed study of microspore and tapetum development over the course of Arabidopsis anther development has revealed the events in pollen wall formation at high resolution with greatly improved preservation of ultrastructural features (Quilichini et al, 2014a). Briefly, pollen wall formation is initiated after microspore mother cells undergo meiosis to generate haploid tetrads surrounded by callose.…”
mentioning
confidence: 99%